PENCEGAHAN PENULARAN TBC DENGAN CARA CUCI TANGAN DAN ETIKA BATUK DI PUSKESMAS BALARAJA - Alfika Safitri; Teguh Handriyo; Riani Amelia Zahara; Muhammad Ramadhan (LPPM Institut Pendidikan Nusantara Global, 2026)
Tuberculosis (TB), commonly known as tuberculosis, is a dangerous airborne disease. It is transmitted by bacteria called Mycobacterium tuberculosis, which spreads through the air when a TB sufferer spits, coughs, or sneezes, which are then inhaled by others. This disease can be prevented by several efforts, including carefully recording TB sufferers and treating them as soon as possible. Furthermore, further efforts include providing literacy or knowledge to the community about how to prevent TB transmission. These efforts include educating families and the wider community about proper handwashing and cough etiquette through Health Education. This community service program aims to increase families' understanding of how to reduce and prevent the spread of TB infection, namely by teaching handwashing and coughing etiquette. The approach implemented was physical and mental well-being education using a pre- and post-testing plan, involving 29 participants within the Balajara Community Health Center. Educational media used included presentations, leaflets, and flipcharts containing information on preventing TB infection transmission through handwashing and coughing etiquette. The results of this activity showed an increase in family knowledge, with the good knowledge group experiencing an increase from 41.37% in the initial test to 86.20% in the final test. It can be concluded that health education is effective in increasing family knowledge regarding preventing TB infection transmission through handwashing and cough etiquette. It is hoped that similar activities can be implemented continuously with the active participation of household members and field implementers.